If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(0) = 6 + -9z Multiply 3 * 0 0 = 6 + -9z Anything times zero is zero. 0 = 6 + -9z Solving 0 = 6 + -9z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '9z' to each side of the equation. 0 + 9z = 6 + -9z + 9z Remove the zero: 9z = 6 + -9z + 9z Combine like terms: -9z + 9z = 0 9z = 6 + 0 9z = 6 Divide each side by '9'. z = 0.6666666667 Simplifying z = 0.6666666667
| 0=y+(x/4)-4 | | 3m2=10 | | 7a+12ab-(2a-b)+3b | | 0=n+x-2 | | 4x^3+4x^2=10 | | 3x-8x+7 | | 218=11x+75 | | 3w=6-9(0) | | -46+4x=14 | | 4x-2x=2+6 | | 3w=6-9(-1.4) | | X^2-13=30 | | 5y-15=19 | | 4(2x+2)=1 | | 9x^2-5xy-6y^2 | | (x-6)(4x^2+x-7)=0 | | -8+9+(-7)= | | 5(y-3)=7 | | (9x-1)(7x+4)=0 | | -7+8(-9)= | | 25=1+4x | | -7=-x+1 | | provecos(2x)=2cos^2x-1 | | 96=-7x-2 | | y-2=-3/8x | | v+12=27 | | x^2-2x-3 | | (7x-1)+(6x-7)= | | 3(z-4)=7z+4 | | 2x+5-3x+40 | | 5n25 | | 6y-9+3-1y= |